Syphilis a Risk Factor for HIV - Chopra, Shashi (Asian Journal of Biological and Life Sciences, 2012)
Sexually transmitted diseases (STD) that cause inflammatory or ulcerative lesions of genital tract act as important cofactor in increasing the risk of transmission of human immunodeficiency virus (HIV) through sexual contact. When syphilis is present there is about 2-5 fold increased rate of acquiring HIV infection. The incidence of HIV can be reduced by preventing and treating the syphilis and other agents causing sexually transmitted infections (STIs). The current prospective study was conducted over a period of three years(2005-2007).A total of 500 blood samples were collected from patients having history of genital ulcers (study group) and 250 persons with history of non ulcerative lesions (control group) referred from skin and STD department of Guru Nanak Dev Hospital in the Integrated Counseling and Testing Centre (ICTC) attached to Microbiology department, Government Medical College Amritsar. Blood samples were collected after obtaining their written consent after pretest counseling. Serum samples were screened for the presence of HIV-1, HIV-2 antibodies and Syphilis by E/R/S and venereal diseases Research laboratory (VDRL) test respectively. VDRL reactive sera were confirmed by Treponema Pallidum Hemagglutination Assay(TPHA). Out of the 500 patients screened 75% were males and 25% were females. Out of these 20(4%) persons were sero reactive for HIV-1infection and none for HIV-2 infection. Thirty three (6.6%) persons were reactive for Syphilis. Co-infection of HIV and syphilis was 45% in HIV sero reactive patients. Out of 250 control group patients 0.8% were sero reactive for HIV-I.HIV sero prevalence rate was significantly higher amongst genital ulcer disease (GUD) patients as compared to patients with history of having non ulcerative lesions .(p<0.001) .It is concluded that HIV prevalence was significantly higher in patients having GUD